Absorption of intramuscular phenobarbitone in children with severe falciparum malaria. - Kuile, F; Nosten, F; Chongsuphajaisiddhi, T; Holloway, P; Maelankirri, L; White, N (Springer-Verlag, 1992)
The absorption of intramuscular phenobarbitone 7 mg.kg-1 was studied in 11 Karen children aged between 1.7 and 11 y with severe falciparum malaria. Eight of the children were comatose. Clinical findings were compared with those in 9 further children with severe malaria of similar age range (four of whom were unconscious), who received an identical placebo. One child, who had received placebo, had repeated convulsions and died 1 h after admission to hospital. The remainder made an uncomplicated recovery. There were no convulsions subsequent to treatment, although the study was too small to assess anticonvulsant efficacy. There was no observable toxicity, but phenobarbitone recipients had a significant tendency to deepen in their level of coma or to become sleepy within the 4 h after drug administration. Phenobarbitone was rapidly absorbed, reaching a mean (range) peak concentration of 34.2 [29.3-42.6] mumol.l-1 in a median (range) of 4 (2.5-12) h. These values are comparable to those previously reported in healthy children and in children with febrile convulsions. Intramuscular phenobarbitone is well absorbed in children with severe malaria; the optimum prophylactic anticonvulsant dose remains to be determined.